2020
DOI: 10.1186/s13643-020-01457-9
|View full text |Cite
|
Sign up to set email alerts
|

Combining angiotensin receptor blockers with chlorthalidone or hydrochlorothiazide – which is the better alternative? A meta-analysis

Abstract: Background: Hypertension is a disease with significant clinical and socioeconomic consequences. The reduction in cardiovascular mortality and morbidity in patients treated for hypertension is directly related to the magnitude of blood pressure reduction. Diuretics have proven useful for the prevention of cardiovascular complications in addition to a long history of safety and efficacy. The main aim for this meta-analysis is to compare the efficacy of the combination of angiotensin receptor blocker (ARB) and ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 62 publications
0
5
0
4
Order By: Relevance
“…In this regard, patients with Stage 2 hypertension (systolic BP ≥ 160 mmHg or diastolic ≥ 100 mmHg), have achieved adequate control of BP only by drug combination therapy. Consequently, the combination of antihypertensive agents with complementary mechanisms of action [3][4][5][6] is recommended. Studies have reported that the addition of hydrochlorothiazide (HCT) improves the BP lowering effects of angiotensin II receptor blockers (ARBs) and, angiotensin-converting enzyme (ACE) inhibitors.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, patients with Stage 2 hypertension (systolic BP ≥ 160 mmHg or diastolic ≥ 100 mmHg), have achieved adequate control of BP only by drug combination therapy. Consequently, the combination of antihypertensive agents with complementary mechanisms of action [3][4][5][6] is recommended. Studies have reported that the addition of hydrochlorothiazide (HCT) improves the BP lowering effects of angiotensin II receptor blockers (ARBs) and, angiotensin-converting enzyme (ACE) inhibitors.…”
Section: Introductionmentioning
confidence: 99%
“…A doença afeta atualmente cerca de 1 bilhão de pessoas ao redor do mundo, com a projeção de aumentar para 1.56 bilhões até 2025, dado o envelhecimento da população. No mundo inteiro, aproximadamente 17 milhões de mortes por ano estão relacionadas a alguma doença cardiovascular, sendo mais da metade dos casos devido a complicações resultantes da hipertensão (Filipova et al, 2020). Por definição, hipertensão arterial sistêmica é uma doença crônica não transmissível definida por níveis pressóricos, em que os benefícios do tratamento (não medicamentoso e/ou medicamentoso) superam os riscos.…”
Section: Introductionunclassified
“…Diversas meta-análises de estudos observacionais demonstram que o risco de morte cardiovascular aumenta continuamente a partir de 75mmHg de pressão diastólica usual e de 115mmHg de pressão sistólica usual, dobrando a cada 10mmHg no primeiro caso e a cada 20mmHg no segundo caso (Filipova et al, 2020). O risco relativo decorrente da elevação da PA acompanha um aumento progressivo do risco absoluto, pois acumulam os riscos basais hipertensão é uma síndrome complexa com múltiplas consequências hemodinâmicas, neuroendócrinas e metabólicas.…”
Section: Introductionunclassified
“…Hypertension is a leading cause of mortality in elderly patients; however, due to the stresses of modern life, even younger people are now suffering from hypertension [1,2]. Globally, about 25% of the population are suffering from hypertension, and this is expected to increase to 30% by 2025 [3]. Different classes of antihypertensive agents are available to control hypertension.…”
Section: Introductionmentioning
confidence: 99%